Impact of the Mobile Telecommunication Network’s Milk Flow Project on the Livelihoods of Pastoralists in Ladugga Grazing Reserve, Kaduna State, Nigeria - Laah, John Gambo (Asian Journal of Agriculture and Rural Development, 2013)
The paper aims at assessing the impact of Mobile Telecommunication Network (MTN) Milk-Flow Project on the livelihoods of pastoralists in Ladugga Grazing Reserve in Kaduna State, Nigeria. A structured questionnaire was administered to 242 pastoralists in Ladugga. To complement the quantitative source of data, Focus Group Discussions (FGDs) and in-depth interviews (IDIs) were conducted to assess the benefits and impact of the Milk Flow Project. A total of four (4) FGD sand four (4) IDIs were held with Fulani pastoralists and stakeholders in Ladugga Grazing Reserve. The mean age for male respondents was 55 years while that of the females was 42 years. The result reveals that the milk-flow project has led to: formation and membership of cooperative societies; significant increase in milk production and consequently income; a reduction in morbidity and mortality rates of cows due to better health seeking behaviours; the development of pasture farms and an increase in school enrolment. The paper suggested the need to encourage more private sector participation in supporting pastoralists’ livelihoods within the grazing reserve systems.